2017
DOI: 10.18632/oncotarget.21942
|View full text |Cite
|
Sign up to set email alerts
|

Identification of potential metabolic biomarkers of cerebrospinal fluids that differentiate tuberculous meningitis from other types of meningitis by a metabolomics study

Abstract: Tuberculous meningitis (TBM) is caused by tuberculosis infection of of the meninges, which are the membrane systems that encircle the brain, with a high morbidity and mortality rate. It is challenging to diagnose TBM among other types of meningitis, such as viral meningitis, bacterial meningitis and cryptococcal meningitis. We aimed to identify metabolites that are differentially expressed between TBM and the other types of meningitis by a global metabolomics analysis. The cerebrospinal fluids (CSF) from 50 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…The technique is used to identify metabolites that are associated with certain physiological or pathological conditions. Several studies have demonstrated significant differences in amino acids and energy metabolism in CSF samples of TBM patients compared with other groups, including patients with viral, bacterial, and cryptococcal meningitis ( 103 106 ). However, the diagnostic accuracy of the metabolites identified was not reported.…”
Section: Potential Of Novel Biomarker-based Approachesmentioning
confidence: 99%
“…The technique is used to identify metabolites that are associated with certain physiological or pathological conditions. Several studies have demonstrated significant differences in amino acids and energy metabolism in CSF samples of TBM patients compared with other groups, including patients with viral, bacterial, and cryptococcal meningitis ( 103 106 ). However, the diagnostic accuracy of the metabolites identified was not reported.…”
Section: Potential Of Novel Biomarker-based Approachesmentioning
confidence: 99%
“…Another similar study ( Zhang et al, 2019 ) included bacterial meningitis (BM) in addition, and found that 23, 6, and 21 metabolites were able to differentiate TBM from VM, BM and meningitis-negative groups, respectively, albeit with a strong overlap between these different groups of differential metabolites. The MS-based metabolomics profiling of adult CSF by Dai et al (2017) included further a cohort of cryptococcal meningitis (CM, n = 16), in addition to TBM (n = 50), VM (n = 17) and BM (n = 17) patients. They reported 13, 16, and nine potential biomarkers, mainly involved in the metabolism of amino acid, lipids and nucleotides, which differentiate between TBM and VM, BM, and CM, respectively.…”
Section: Biomarkers Based On Host Responsesmentioning
confidence: 99%
“…Metabolomics research has identified several potential metabolic biomarkers of CSF that can help distinguish different types of meningitis. According to different studies, glutamate and cysteine may be potential metabolic markers of CSF that can help distinguish CM from tuberculous meningitis ( 96 ). Similarly, another study evaluated the metabolic status of lung epithelial cells that were infected with C. neoformans .…”
Section: Evidence Of Ferroptosis In CMmentioning
confidence: 99%